Coastal MSME Transformation: Public Private Partnership and Blue Investment for Informal Development - Nurvairah Dwi Febrianingsih; Adel Zain Filadelfia; Redita Salsabila Aldama (Pattimura Proceeding, 2026)
The concept of the blue economy has reemerged as a mainstream development paradigm, yet the optimization of seaweed potential in South Sulawesi remains constrained by structural challenges, particularly the limited institutional capacity of village-owned enterprises and coastal MSMEs to access sustainable investment schemes. In addition, the absence of effective collaborative governance continues to hinder the integration of key actors in developing the seaweed industry in Pangkajene dan Kepulauan Regency. This study aims to formulate an applicable development approach by integrating the Public–Private Partnership (PPP) model with a Blue Investment scheme as a strategic framework to strengthen the village-based seaweed industry. The integration of PPP and Blue Investment is expected to enhance governance quality, expand access to financing, and promote a sustainable seaweed supply chain. This research employs a qualitative approach through in-depth interviews, non-participatory observation, and document analysis, with data validity ensured through triangulation. Thematic analysis is applied to identify patterns of institutional collaboration, financing mechanisms, and sustainability practices along the seaweed value chain. The findings indicate that integrating PPP and Blue Investment can improve institutional capacity, increase value chain efficiency, and encourage environmentally responsible cultivation practices. These findings support rural economic development and sustainable coastal MSMEs.